The Rushdiyye School in Rawandz and its most prominent problems 1868-1916 - Ahmed, Bzhar Othman (Journal of University of Human Development, 2024)
Throughout the history, science and scholars have held a prominent position within Kurdish society. During ancient times, mosques, madrassas, and chambers served as the primary hubs for scientific knowledge and educational institutions. However, during the final phase of Ottoman administration in Kurdistan, the state officially established schools, including one in the city of Rawandz. The state covered the expenses of these schools, including teachers’ salaries and the provision of educational materials for students. However, in contrast to other educational institutions in Rushdiya, the Rushdiya school in Rawandz exhibits several deficiencies and challenges. The subject matter revolved around education, students, and teachers. In this study, many scientific methodologies were employed, including historical analysis and the examination of textual materials as the primary source. Additionally, supplementary scientific sources such as books and research papers were utilized. Academic fields such as master’s and doctorate theses, along with the use of comparative techniques sources and official calendars and papers of the Ottoman state, offer comprehensive insights into his life and accomplishments. This research aims to scientifically examine the Rushdieh School of Rawandz and the prominent issues that arose between 1868 and 1916. Despite these challenges, the school played a significant role in advancing the scientific interests of Rawandz and fostering the development of a new generation.